2017
DOI: 10.1080/15376516.2017.1344338
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of quercetin on nicotine induced oxidative stress in ‘HepG2 cells’

Abstract: Nicotine is a natural component of tobacco plants and is responsible for the addictive properties of tobacco. Nicotine has been recognized to result in oxidative stress by inducing the generation of reactive oxygen species (ROS). The purpose of this work was to estimate the hepatotoxicity effect of nicotine on viability and on antioxidant defense system in cultures of HepG2 cell line and the other hand, ameliorative effect of quercetin (Q) as an antioxidant was analyzed. Nicotine induced concentration dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…Therefore, we investigated the direct effects of three doses (10 − 11 , 10 − 8 and 10 − 6 M) of nicotine on global genomic DNA methylation and DNMTs gene expression in HESC. The rationale for using 10 − 11 , 10 − 8 and 10 − 6 M concentrations were that we have reported previously that the nicotine doses below 10 − 6 M are safe for using in the in-vitro model of human cells [30,35]. Our results indicated that treatments of HESC with 10 − 11 and 10 − 8 M of nicotine significantly decreased the level of DNMT1 gene expression by 98 and 86.5% in comparison to control cells ( Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we investigated the direct effects of three doses (10 − 11 , 10 − 8 and 10 − 6 M) of nicotine on global genomic DNA methylation and DNMTs gene expression in HESC. The rationale for using 10 − 11 , 10 − 8 and 10 − 6 M concentrations were that we have reported previously that the nicotine doses below 10 − 6 M are safe for using in the in-vitro model of human cells [30,35]. Our results indicated that treatments of HESC with 10 − 11 and 10 − 8 M of nicotine significantly decreased the level of DNMT1 gene expression by 98 and 86.5% in comparison to control cells ( Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Quercetin protects the nerves, brain, or other body cells from oxidation-induced damage by regulating the antioxidant levels [31]. Quercetin prevents free radicals and enhances the body's antioxidant defense systems and therefore reduces oxidative stress, including the production of nicotine-induced ROS for the treatment of diseases such as nicotine addiction [38]. In vivo studies have shown that quercetin has antioxidant and hepatoprotective activity against acute hepatic injury caused by tertiary butyl hydrogen peroxide.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Moreover, EGCG has been shown to chelate transition metals that increase ROS levels by the Fenton reaction and to indirectly upregulate the expression of phase II antioxidant enzymes [50]. Numerous other compounds present in the TE and LE extracts, such as the caffeic acid derivatives, quercetin, and its esters, have also been shown to have a protective effect against nicotine induced cytotoxicity [9,10,[51][52][53]. .…”
Section: Cytocompatibility and Cytoprotective Effect Of Le And Te Agamentioning
confidence: 99%